Pemanfaatan Citra Satelit dan SIG Guna Menentukan Jalur Evakuasi Tsunami di Wilayah Pulau Bali Bagian Selatan - Teguh Budiman; Dadang Gunawan; Setyo Budiyanto; R.A.G. Gultom (Departement of Mathematics Education, 2023)
Abstract The State of Indonesia is a country that is traversed by the Ring of Fire, which means that the State of Indonesia has the privilege that there are many volcanoes in Indonesia. This is also caused by the existence of a subduction line that surrounds Indonesia from the west end to the east end, making Indonesia a country frequently hit by earthquakes. The purpose of this research is to make evacuation routes more efficient and effective in terms of safety and smoothness where these independent evacuation routes are supported by new theories that are more supportive then new tools that can support research and also data that which can show the differences that are useful in making this evacuation route map. The method used in this study basically emphasizes quantitative research methods, although qualitative ones must still be used. This research method uses quantitative and qualitative methods. Quantitative research uses statistics in testing the data so that the relationship between variables can be obtained objectively. Qualitative research is an attempt by researchers to collect scientific data in a descriptive, verifiable and grounded research format so that the results can be accounted for